(untitled) (Revista Científica Compendium, 2020)
The aim of this research is to specify the conceptualization of Inflation as a macroeconomic phenomenon and to approach the causes that originated it in Barquisimeto City, Lara State, from the perspective of specialists in economic matters, which are constituted by professors belonging to the Department of Economics of the Universidad Centroccidental “Lisandro Alvarado”. The methodology used was descriptive. It was based on the data provided by the Central Bank of Venezuela and the National Institute of Statistics, which was available until the year 2019. In addition, a theoretical review of various approaches that explain the origin of Inflation was carried out and then contrasted them with the specialists’ opinion using a questionnaire. The study found the inflation rate in Barquisimeto in period 2010-2015 has been growing due to the low productivity and imbalance achieved by the loss of incentive by entrepreneurs, being one of the most expensive cities in the country.